Changing Education Leadership, Innovation and Development in a Globalizing Asia Pacific - Mason, Mark.; Hershock, Peter D.; Hawkins, John N.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
This book responds to the growing unease of educators and non-educators alike about the inadequacy of most current educational systems and programs to meet sufficiently the demands of fast changing societies. These systems and programs evolved and were developed in and for societies that have long been transformed, and yet no parallel transformation has taken place in the education systems they spawned. In the last twenty years or so, other sectors of society, such as transportation and communications systems, have radically changed the way they operate, but education has remained essentially the same. There is no doubt: education needs to change. To those ready to accept this challenge, this book represents a welcome guide. Unlike most books on educational policy, this volume does not focus on improving existing educational systems but on changing them altogether. Its focus is not on doing things better, but on doing better things; not on doing things right, but on doing the right things to prepare students for a fast changing interdependent world.
The Context and Imperatives for Paradigmatic Change in Education -- Introduction: Challenges in the Leadership of Innovation and Development in Education in a Globalizing Asia Pacific -- Globalization and Education: Characteristics, Dynamics, Implications -- Rethinking Educational Aims in an Era of Globalization -- Multiculturalism, Shared Values, and an Ethical Response to Globalization -- Education and Alleviating Poverty: Educating for Equity and Diversity -- Outcomes and Opportunities for Change: Education in a Renewing Asia -- The Intractable Dominant Educational Paradigm -- Globalization and Paradigm Change in Higher Education: The Experience of China -- Pulling Together amid Globalization: National Education in Singapore Schools -- Education in the Years to Come: What We Can Learn from Alternative Education -- Leadership in Changing the Way Education Changes -- Leadership in the Context of Complex Global Interdependence: Emerging Realities for Educational Innovation -- The Changing Role of Leadership (or A Changing Leadership for a Changing World) -- Interconnections Within and Without: The Double Duty of Creative Educational Leadership -- Unraveling Leadership: 'Relational Humility' and the Search for Ignorance.
Keywords: EDUCATION; EDUCATION -- PHILOSOPHY; EDUCATION; EDUCATION (GENERAL).; ADMINISTRATION, ORGANIZATION AND LEADERSHIP; SOCIOLOGY OF EDUCATION; EDUCATIONAL PHILOSOPHY; INTERNATIONAL AND COMPARATIVE EDUCATION; EDUCATIONAL POLICY AND POLITICS